Based on the given parameters, the value of the function h(-1) is -1
The equation of the function is given as:
h(t) =-t^2 + t + 1
The function is given as:
h(-1)
This means that t = -1
So, we substitute t = -1 in the equation h(t) =-t^2 + t + 1
h(-1) =-(-1)^2 + (-1) + 1
Evaluate the exponent
h(-1) =-1 - 1 + 1
Evaluate the like terms
h(-1) = -1
Hence, the value of the function h(-1) is -1
Read more about functions at:
https://brainly.com/question/1415456
#SPJ1
Complete question
Consider the following function definition, and calculate the value of the function
h(t) = −t2 + t + 1 h(−1)